Peningkatan Kemampuan dalam Penyesuaian Diri Anak di Lingkugan Taman Kanak-Kanak Bunda Kartika Deli Serdang, Sumatera Utara - Arys Fadillah; Selvia Andraini; Citra Irawan; Surya Zulfachrinal Tanjung; Sani Susanti (Universitas Maritim AMNI Semarang, 2024)
This research is motivated by the fact that nearly 70% of children who are newly enrolled and start learning at Bunda Kartika Kindergarten in Patumbak, Deli Serdang, have difficulty adjusting to the new learning environment. This stage of learning in kindergarten is their first step into formal education. According to the Ministry of Education and Culture Regulation No. 137 of 2014 on national standards for early childhood education (PAUD), it sets national standards for PAUD, including aspects of child development that must be met during the learning process. These standards cover various aspects of child adjustment such as socio-emotional, language, cognitive, and motor skills. This research aims to identify the nature of adjustment problems occurring in kindergartens and early childhood education by understanding the aspects of adjustment and the supporting and inhibiting factors for new students in adapting to the new environment. The research method used is a descriptive qualitative method, where the researcher conducts objective interviews and environmental observations. Data collection techniques include document review, observation, and interviews. The results of the study indicate several issues related to children's adjustment, ranging from psychological factors, prenatal environment, parenting styles, to socialization problems in the school environment. These factors significantly impact early childhood development and require special attention in the context of preschool education.